2008
DOI: 10.1016/j.vetimm.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of FIV infection

Abstract: Feline immunodeficiency virus (FIV) is an important viral pathogen worldwide in the domestic cat, which is the smallest animal model for the study of natural lentivirus infection. Thus, understanding the molecular mechanisms by which FIV carries out its life cycle and causes an acquired immune deficiency syndrome (AIDS) in the cat is of high priority. FIV has an overall genome size similar to HIV, the causative agent of AIDS in man, and shares with the human virus genomic features that may serve as common targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 118 publications
(106 reference statements)
1
28
0
2
Order By: Relevance
“…Viral load is a key marker of in vivo viral burden, and its measurement in blood is a useful indicator of systemic disease status (38,39). Animals that were repeatedly exposed to LPS showed signs of sickness behavior for ∼1-2 h after injection, as evidenced by reduced motor activity, sleep, and ruffled coat, but promptly recovered in all cases.…”
Section: Systemic Lps Exposure Reduced Viral Burdenmentioning
confidence: 99%
“…Viral load is a key marker of in vivo viral burden, and its measurement in blood is a useful indicator of systemic disease status (38,39). Animals that were repeatedly exposed to LPS showed signs of sickness behavior for ∼1-2 h after injection, as evidenced by reduced motor activity, sleep, and ruffled coat, but promptly recovered in all cases.…”
Section: Systemic Lps Exposure Reduced Viral Burdenmentioning
confidence: 99%
“…Since the discovery of human immunodeficiency virus type 1 (HIV-1) in 1982 there is an urgent need for animal models to study the pathogenesis of HIV-1 infection and possibilities for interventional strategies (Elder et al, 2008). FIV was descript in 1987, and since then, FIV has been proposed as a model for HIV studies, because, among non-primate vertebrates, FIV infection in the cat may be the closest model of HIV infection and acquired immunodeficiency syndrome (AIDS).…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) X Feline Immunodmentioning
confidence: 99%
“…FIV and HIV share many features in their genomes in comprising three major open reading frames (ORF), gag, pol and env, especially in the pol gene and FIV also has a very similar life cycle to that of HIV (Table 2) (Savarino et al, 2007;Elder et al, 2008;Elder et al, 2010 The similarities and discrepancies in the physiopathology of feline and human viruses in their respective natural hosts presents striking analogies, and several intriguing differences (Tables 3 and 4). FIV and HIV share a common pattern on clinical signs, having initially a nonspecific acute phase, followed by an asymptomatic phase and a phase in which the immune system is compromised and the animal is subjected to secondary infections (Sellon e Hartmann, 2006;Gunn-Moore & Reed, 2011;Hartmann, 1998;Hartamann, 2011;Magden et al, 2011;O'Brien et al, 2012).…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) X Feline Immunodmentioning
confidence: 99%
“…32,39-44 Despite having very little sequence homology with HIV-1, we and others have shown that the molecular mechanisms and organization of functional domains for FIV virion assembly and release, proteolytic maturation of Gag and Env, Env-mediated receptor/co-receptor binding and membrane fusion, reverse transcription, integration, latency, Rev-dependent export of genomic RNA, and targeting of antiviral restriction factors are all highly conserved with those of HIV-1 and other primate lentiviruses. 32,44-62 For example, the PSAP motif in the C-terminal p2 domain of FIV Gag functions equivalently to the PTAP motif in HIV-1 Gag p6 in its role in FIV release and direct interaction with TSG101. 5,46 Unlike HIV-1, however, FIV does not contain a secondary YPXnL-type late domain and is insensitive to agents that would disrupt interactions with the Alix-V domain.…”
Section: Introductionmentioning
confidence: 99%